Working Capital Management Practices among SMEs Owners-Managers: A Qualitative Inquiry - Imelda Jeremiah Mville Mville; Dr. Mushumbusi Kato; Dr. Gabriel Vitus Komba (Universitas Airlangga, 2026)
Background: SMEs are considered critical to creating employment opportunities, driving economic development, and alleviating poverty. Nevertheless, they often struggle to manage their finances effectively. This paper examines the working capital management practices of SME owner-managers, focusing on cash, inventory, receivables, and payables. Objective: The study aims to evaluate working capital management practices employed by SME owner-managers in their operations. Method: Semi-structured interviews with 15 SME owner-managers in the Tanzanian timber industry in Keko, Dar es Salaam, were conducted as part of a qualitative research strategy. Results: Informal financial management practices used by SMEs include manual product inventory records, trust credit, and cash flow estimation. Even when these approaches provide operational flexibility, SMEs face inefficiencies, liquidity constraints, and financial instability. Conclusion: The study argues that SMEs should be more formal in managing their working capital, e.g., by adopting electronic inventory management systems, improving cash flow forecasts, and establishing formal credit procedures. By applying these strategies, SMEs can minimize risks, improve overall sustainability, and enhance financial control. Keywords: Working Capital Management Practices, SMEs Financial Practices, Financial Sustainability.